The Routledge anthology of poets on poets : poetic responses to English poetry from Chaucer to Yeats - Hopkins, David, 1948- (Routledge, 1994)
A comprehensive record of the history and progress of English poetry. It collects together writings by all the major and some of the lesser-known figures from Chaucer to Yeats, demonstrating their vivid responses to each other.